FAVOURED STATES OF PALAEOSTRESS IN THE EARTH'S CRUST: EVIDENCE FROM FAULT-SLIP DATA - Lisle R.J.; Orife T.O.; Arlegui L.; Liesa C.; Srivastava D.C. (My University, 2006)
In a major survey of published palaeostress estimates obtained by the use of fault-slip data, over 2000 stress tensors from shallow crustal levels have been compiled. The results are derived from regions where deformation is dominated by brittle processes, and consist of incomplete stress tensors in which the orientations of the principal stresses (σ1≧σ2≧σ3) are known, together with the stress ratio, Φ=(σ2-σ3)/(σ1-σ3). The orientations of the stress axes display a preferred orientation, with a tendency for one of the axes to be vertical. This accords with Anderson's assumed 'standard state' stress configuration near to the Earth's free surface. Although the tendency is strong, there are frequent deviations from the arrangement; in 25% of cases the steepest stress axis deviates by more than 25° from the vertical. In undertaking studies of palaeostress it would be therefore unwise to use methods that assume a priori one vertical stress axis unless previous local results indicate this to be the case. Normal, strike-slip and thrust stress arrangements (with σ1, σ2 and σ3 as the steepest stress, respectively) occur in the database with frequencies approximately in the ratio 2:2:1. In the compiled results, the raw stress ratios, Φ, which have a theoretical range from 0 to 1, show a lack of very high values and, to a lesser extent, very low values. This suggests that triaxial stress states are more common than axial compression deviatoric stress and axial tension deviatoric stress. However, this relative abundance of triaxial stress states is considered to be a natural feature of a uniform distribution of stress tensors. In addition, there is a marked bias in the collated ratios towards values less than 0.5 and this is expressed by an overall mean Φ of 0.39. Several possible explanations for the distribution of stress ratios are discussed. These explanations are related to the tendency for tectonic deformation to be of plane strain type coupled with volume change and to the fact that gravitational loading makes an important contribution to the state of stress in the crust. © 2006 Elsevier Ltd. All rights reserved.
Keywords: FAULTS; POISSON'S RATIO; SLIP; STRESS RATIO; STRESS SURVEY